Increasing compliance with alcohol service laws in community sporting clubs in Australia. (5th April 2021) - Kremer, Peter; Crooks, Nicholas; Rowland, Bosco; Hall, Jessica; Toumbourou, John W.
Abstract: Introduction: Many community sporting clubs in Australia sell alcohol, but many do not comply with laws that require verification of age and forbid underage alcohol sales. This study aimed to assess the effectiveness of an intervention that incorporated sales monitoring and community awareness raising to improve compliance with alcohol service regulations in community sporting clubs. Methods: Non‐randomised community trial in 'matched' intervention and comparison communities. A total of 50 sporting clubs from two metropolitan and two regional areas in Victoria, Australia, were selected, and baseline and follow‐up purchase observations completed during 2018. Youth who looked underage were monitored as they attempted to purchase alcohol. Intervention clubs received feedback letters regarding staff sales behaviour. Other intervention actions included building awareness of underage supply of alcohol and media coverage of baseline observations. Results: Observations were completed at 46 clubs (intervention = 24; comparison = 22) at baseline and 39 (intervention = 24; comparison = 15) at follow up. Compliance was low but improved at follow up for both groups for age verification (intervention +12.5%; comparison +8.5%) and non‐supply of alcohol (intervention +12.5%; comparison +10.6%); but no significant intervention effects were found. Discussion and Conclusions: Findings indicated low compliance with age verification checks and underage alcohol sales laws at baseline. Promising improvements in compliance were observed at follow up; however, 'spillover' of intervention activities may have compromised ability to detect significant intervention effects. Further intervention effort and evaluation is recommended to encourage alcohol sales compliance in community sporting clubs.